Studi Polimerisasi Ester Dari Asam Lemak Sawit Distilat (ALSD) Menggunakan Inisiator Benzoil Peroksida 0,4 % - Fitra Annisa; Zuchra Helwani; Bahruddin Bahruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Palm Fatty Acid Distillate (PFAD) is a byproduct from palm oil processing industry that used as raw material for synthesis polyester based vegetable oil. The purpose of the research is to study polymerization reaction of ester from PFAD using inisiator benzoyl peroxide 0,4%. There are three step reaction in this research that was esterification, polymerization, and polyesterification. The esterification stage was done at temperature 70oC, reaction time 2 hours, reactant ratio 1:8 (ALSD : metanol), and concentration catalyst H2SO4 1% (w/w) ALSD. Polymerization stage was done at variation of temperature 120, 130, and 140oC and variation reaction time 3, 4, and 5 hours using initiator benzoyl peroxide 0,4% (w/w) methyl ester. Polyesterification stage was done at temperature 175-200oC, reaction time 4 hours, and ratio reactant 1:1 (polymerized methyl ester : ethylene glikol). Product was analyzed by using FT-IR, GC-MS, and viscosity. The result of FT-IR showed that vinyl group was presence who indicated double bonding was presence and polymerization was not occur. The result of GC-MS showed there had no change of molecular weight. And product with temperature 130oC and reaction time 5 hours has higher viscosity value.Keyword : benzoyl peroxide, esterification, PFAD, polymerization